Strategi Pemagaran dalam Ujaran Bahasa Jepang: Analisis Wawancara Jalanan Kanal Youtube Ask Japanese - Syahid, Abdurrahman; Filia, Filia (Vocational College of Diponegoro University, 2023)
This study reviews the hedging phenomena in Japanese speech found in street interview Ask Japanese. The hedging can be seen in interviewees’ answers to the interviewer’s questions. The data source used in this study is videos uploaded to Youtube by channel Ask Japanese. The reason for choosing such data source is that the videos are recorded impromptu, and thus, they show the realization of hedging in utterance naturally without any make-up. There are, in total, two videos of interview that is analyzed. The theories used are hedging as semantic phenomenon and hedging as pragmatic phenomenon. This research employs qualitative method that is involving analyzing data that have been transcribed and codified beforehand. In the videos used, there are 234 cases of hedging found. After keen observation, it is revealed that those cases of hedging are not realized in the same way. They can be classified into 6 types of strategies according to their realization in speech, namely (i) hedging by emphasizing subjectivity, (ii) hedging by expressing uncertainty, (iii) hedging by creating common ground, (iv) hedging by approximation, (v) hedging by exemplification, and (vi) hedging by downtoning.